THE RELATIONSHIP OF MOTHER'S CHARACTERISTICS AND HUSBAND'S SUPPORT REGARDING MOTHER'S PARTICIPATION IN PREGNANCY CLASS IN MEDANGASEM VILLAGE, KARAWANG DISTRICT YEAR 2023 - Yuningsih, Kasti; Futriani, Elfira Sri (HEARTY, 2024)
Class This Pregnant Mother is government program used as a means to learn together about health for pregnant women. Activity the can form stare advance in group Which aim For increase knowledge And Skills moms about pregnancy, maintenance pregnancy, preparation face labor, maintenance moment postpartum, newborn care, myths during pregnancy, childbirth, postpartum nor maintenance baby new born, as well as diseases Which join And certificate birth. This study aims to determine the relationship between maternal characteristics and husband's support with maternal participation in classes for pregnant women in Medangasem Village. This research design uses cross method sectional analytic with a quantitative approach, namely carrying out measurements or observations on variable free (independent) with variable depends (dependent) done during Which The same sampling of 35 pregnant women from December 202 3 – January 202 4 in the region Work Public health center Medangasem Karawang.Results Analysis using the Shapiro-Wilk data test uses the statistical test used in this research is the Chi-Square test to obtain a p-value of 0.025 which has a lower value than the p-value <0.05 so that means Ha is accepted It means It can be said that there is a relationship between husband's support with the mother's participation in attending pregnancy classes in Medangasem village. Expected power health especially midwives can increase visits to pregnant women's classes by continuing to socialize pregnant women's classes as a whole in language that is easy for pregnant women to understand because there are still so many pregnant women at a relatively young age. young, low education and lack of birth experience.